O corpo do senhor : um estudo sobre a compreensão da Eucaristia em Francisco de Assis a partir de seus escritos - Lima, Jairo Silva de (2014)
Francis of Assisi (1182-1226) was a pious man of the 13th century who wished ardently follow the footsteps of the poor and crucified Christ. He lived in a historic moment of many transformations, marked especially by the phenomenon of urbanization; and sought sincerely live the Gospel in penance and itinerancy, in the midst of a variety of other movements that sought reforms in the structures of the Church and society. Francis of Assisi left many writings and a group of these stands out by the references that he makes about the Eucharist, the so-called writings of Eucharistic Cycle. To understand the contents of these writings was necessary to penetrate through the history of Eucharistic Theology for the genesis of his assertions and expressions of faith. This entering into the history of Eucharistic theology revealed that faith in the real presence was shaken in historic moments of synthesis and changes of mentality. Such is the case of the process known as Germanization; followed by the feudalization and finally the urbanization. Amid all these processes, the Church needed to give adequate responses, as well as to reaffirm through the dogmas of faith truths that are valid for men of all times and places.